Relationship Between Social Support, Religiosity, and Academic Expectation on Suicidal Ideation Among University Student - Ismail, Fadillah; Adibah Abdul Kadir; Zahuren Abdul Kadir (Advances in Humanities and Contemporary Studies, 2022)
According to the report by the Royal Malaysian Police (PDRM) found that a total of 638 suicides were reported in Malaysia between January and July 2021, an increase of 143% compared to the same period last year. Suicide is the fourth leading cause of death in an adolescent aged 15-19 years and for every single suicide case, there are more cases involving suicide attempted. The purpose of this study is to identify the level of suicidal ideation and the relationship between social support, religiosity, academic expectation and suicidal ideation among university student. Quantitative approach is used for this study and survey questionnaire as the research tool. This study focused on university students as the respondents by using random sampling technique. The questionnaire distributed for 350 set, and only 301 respondents answered the questionnaire. Statistical Package for Social Science (SPSS) Program was used for descriptive analysis. The finding of the study is that most of the students have moderate level of suicidal ideation. The suicidal ideation is also has a significant and positive relations with social support, religiosity and academic expectation. In a nutshell, the suicidal ideation among university students is moderate. It also can be conclude that suicidal ideation has significant and positive relationship towards social support, religiosity and academic expectation. The finding of this study provides a deeper understanding of suicidal ideation in the future.